Influence of corporate social networks on the innovative receptivity of personnel, by example of Bitrix24 software (VO OVEN Ltd) - Dyuzhev, V. G.; Boichenko, O. I. (ВД "Академперіодика", 2019)
Introduction. Increasing the innovative receptivity (IR) of personnel using intra-corporate social networks (CSN) is a pressing problem. Problem Statement. Currently, Ukraine is actively discussing the problems of digital transformations in the economy, as well as the importance of digital initiatives and research in this industry, as evidenced by the Conception for the development of the digital economy and society of Ukraine for 2018—2020 and a respective action plan for the implementation of this Conception (approved by the Cabinet of Ministers of Ukraine) adopted in January 2018. Theoretical and practical issues of analyzing the impact of intra-corporate communications in the CSN on the development of competencies and IR of employees have not been fully developed so far. Purpose. To identify trends and effect of CSN on personnel ІR by example of Bitrix24 software in VO OVEN Ltd. Materials and Methods. Methods for comparative analysis of local and international CSN operation in Ukraine and throughout the world; analysis of the use of Bitrix24 software in the Ukrainian company. Results. The ways to increase the IR of personnel using CSN and classic Internet portal have been shown. The CSN services in the system of corporate business tasks and their authentication with conventional human resources management system have been analyzed. The domains of effective CSN application in American corporations and in VO OVEN Ltd (Ukraine) have been compared. Data summary of Bitrix24 information messages (live news feed) in VO OVEN Ltd for 2017 and for the 1st quarter of 2018 has been given. Based on research results, a new HRMS function has been implemented to show the dataware of personnel and the realization of technical and economic processes for developing CSN under current conditions. Conclusions. To ensure an adequate perception of digital technologies on industrial corporations, Ukraine needs highly qualified personnel with digital skills and competences. One of the options to develop these competences is to use CSN.

Вступ. Актуальним питанням підвищення інноваційної сприйнятливості (ІС) персоналу є використання внутрішньофірмових корпоративних соціальних мереж (КСМ). Проблематика. На сьогодні в Україні відбувається активне обговорення проблем цифрових трансформацій економіки, а також важливості цифрових ініціатив і наукових досліджень у цій галузі, про що свідчить прийнята у січні 2018 року Концепція розвитку цифрової економіки та суспільства України на 2018—2020 рр. та відповідний план заходів щодо реалізації цієї Концепції (затверджений Кабінетом Міністрів України). Теоретичні та практичні питання аналізу впливу внутрішньофірмових комунікацій у КСМ на розвиток компетенцій та ІС співробітників підприємств, на сьогодні, опрацьовані не повною мірою. Мета. Визначення тенденцій і закономірностей впливу КСМ на ІС персоналу на прикладі ПЗ Bitrix 24 в компанії ТОВ «ВО Овен». Матеріали й методи. Методи порівняльного аналізу роботи вітчизняних та закордонних КСМ в Україні та світі; аналіз використання ПЗ Bitrix 24 в українській компанії. Результати. Показано можливості підвищення IC персоналу при використанні КСМ і класичного інтернет-порталу. Проаналізовано сервіси КСМ в системі бізнес-завдань організації та їх ідентифікація з традиційними системами управління персоналом (СУП). Приведено порівняння ефективних сфер застосування КСМ в американських компаніях і в ТОВ «ВO ОВЕН» (Україна). А також наведено підсумкові дані інформаційних повідомлень ПЗ Bitrix 24 (жива стрічка) в компанії ТОВ «ВO Овен» за 2017 р. і за І квартал 2018 р. За результатами дослідження введено нову функцію СУП, яка показуватиме інформаційне забезпечення персоналу, реалізацію техніко-економічних процесів для розвитку КСМ в нинішніх умовах. Висновки. Для забезпечення адекватного сприйняття цифрових технологій на промислових підприємствах України потрібні кваліфіковані кадри, які володіють цифровими навичками та компетенціями. Одним з варіантів розвитку таких компетенцій є використання КСМ.
Вплив на інноваційну сприйнятливість персоналу корпоративних соціальних мереж, на прикладі програмного забезпечення Bitrix24, в компанії ТОВ "ВО ОВЕН"
Keywords: innovative receptivity; corporate social networks; Bitrix24; сприйнятливість інноваційна; корпоративні соціальні мережі